Development of a Ready to Consume Sweetened Fish Powder for Children - Varghese John (Department of Processing Technology, College of Fisheries, 2004)
A sweetened snack food was developed from a lean and cheap fish (Priacanthus hamrur Forskal, 1775) for children, to meet their increased requirements for protein and energy, corresponding to their higher growth rate and physical activities. The food was planned to be attractive & palatable to children; without any fish flavour and bones; and that could be stored at room temperature. The product was developed from surimi, since the latter was devoid of all the undesirable characteristics of fish flesh but retained its nutritive qualities. Surimi was solubilized with salt, into a protein-sol and sweetened it with sucrose, which also had a protective effect on protein from heat-denaturation. The sol was dried, ground and flavoured with cocoa- powder. The most preferred levels of sucrose and cocoa-powder were standardized by sensory evaluation of samples prepared with different levels of sucrose and cocoa powder. The final product was prepared by the standardized procedure, packed in polyester-LDPE laminated pouches and stored. Children's response to [he product was also tested. A 90day's storage study was conducted and the quality changes during storage were monitored periodically. There were no significant variations in the pH and TVBN values (P>O.05). The moisture and TBARS values showed a statistically significant increase. A decreasing trend was observed in the aerobic plate counts. The sensory quality parameters like odour, texture, taste and overall acceptability, did not decrease significantly. The product was acceptable throughout the storage period.